2008
DOI: 10.1063/1.2987366
|View full text |Cite
|
Sign up to set email alerts
|

A crossed molecular beam study on the synthesis of the interstellar 2,4-pentadiynylidyne radical (HCCCCC)

Abstract: Crossed molecular beam experiments are performed to elucidate the synthesis of the 2,4-penta-diynylidyne [HCCCCC(X (2)Pi)] radical under single collision conditions--a crucial reaction intermediate to form polycyclic aromatic hydrocarbons and carbonaceous nanostructures in the interstellar medium and in combustion flames. The experiments demonstrate that the chemical dynamics of ground state carbon reacting with diacetylene [HCCCCH(X (1)Sigma(g)(+))] are indirect and proceed via addition of the electrophilic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Test experiments showed that tricarbon molecules have a significant entrance barrier upon reacting with diacetylene of about 80 kJ mol −1 ; therefore, under our experimental conditions, tricarbon does not react with diacetylene. The lighter carbon ͑12 amu͒ and dicarbon reactants ͑24 amu͒ react with diacetylene; 41,42 due to the heavier cyano radical ͑26 amu͒, carbon and dicarbon reactions lead only to products which are lower in mass by 2 and 14 amu compared to those formed in the reaction of cyano radicals with diacetylene. Consequently, neither dicarbon nor carbon atoms interfered in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Test experiments showed that tricarbon molecules have a significant entrance barrier upon reacting with diacetylene of about 80 kJ mol −1 ; therefore, under our experimental conditions, tricarbon does not react with diacetylene. The lighter carbon ͑12 amu͒ and dicarbon reactants ͑24 amu͒ react with diacetylene; 41,42 due to the heavier cyano radical ͑26 amu͒, carbon and dicarbon reactions lead only to products which are lower in mass by 2 and 14 amu compared to those formed in the reaction of cyano radicals with diacetylene. Consequently, neither dicarbon nor carbon atoms interfered in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The prototype C͑ 3 P͒ +C 2 H 2 ͑acetylene͒ reaction 45,46 has been intensively studied experimentally and theoretically, since the neutral-neutral reactions 47,48 between atomic carbon and unsaturated hydrocarbons are considered an important synthetic route to complex molecules in interstellar medium. Recently, we examined 49,50 the reaction next in line, C͑ 3 P͒ +HC 4 H ͑di-acetylene͒. The reaction of carbon atom with the polyynes, HC 2n H, could also be viewed as a mechanism for the formation of C 2n+1 H and HC 2n+1 H isomers and thus the depletion of the polyynes.…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated C 5 hydrocarbons are of great interest for the physical, theoretical, and combustion chemistry and astrochemistry because they can serve as potential precursors to polycyclic aromatic hydrocarbons (PAHs) both in high-temperature environments, such as in combustion flames and circumstellar envelopes of dying carbon stars (IRC +10216), and under ultracold conditions, for example, in cold molecular clouds like TMC-1 and OMC-1. For instance, high concentrations of C 5 species have been observed in fuel-rich flames. The most systematic study of hydrocarbon-rich flames with allene and propyne, cyclopentene, and benzene as the fuels by Hansen and co-workers has identified, by means of molecular-beam mass spectrometry sampling via tunable vacuum ultraviolet (VUV) synchrotron photoionization, the presence of a broad range of C 5 H x molecules ( x = 2–6, and 8), including C 5 H 2 (1,2-cyclopentadien-4-yne), C 5 H 3 (2,4-pentadiynyl-1, 1,4-pentadiynyl-3, and cyclopenta-1,2,3-triene radicals), C 5 H 4 (1,2,3,4-pentatetraene, penta-1,2-dien-4-yne, 1,3-pentadiyne, and 1,4-pentadiyne), C 5 H 5 (cyclopentadienyl radical), C 5 H 6 (1,3-cyclopentadiene, 1-penten-3-yne, 3-penten-1-yne, and pent-1-en-4-yne), and C 5 H 8 (1,3-pentadiene, cyclopentene, 2-pentyne, and 1,4-pentadiene). , Two C 5 H 3 isomers (2,4-pentadiynyl-1 and 1,4-pentadiynyl-3) and two C 5 H 5 isomers (1-vinylpropargyl and cyclopentadienyl, c -C 5 H 5 ) were also detected in benzene/oxygen flames . Alternatively, in deep space, the highly reactive pentynylidyne radical (C 5 H) and the C 5 molecule have been discovered in the envelope of the carbon star IRC+10216; the former has also been synthesized in the laboratory via crossed molecular beams of ground-state carbon atoms [C­( 3 P)] and diacetylene (C 4 H 2 ) . Previously, experimental and theoretical studies of this and other groups have demonstrated that the C 5 H x species ( x = 3–6) can be produced via neutral–neutral bimolecular reactions, such as C­( 3 P) + C 4 H 4 (vinylacetylene) → C 5 H 3 + H, C 2 (X 1 Σ g / a 3 Π u ) + C 3 H 4 (methylacetylene and allene) → C 5 H 3 + H, C 2 (X 1 Σ g / a 3 Π u ) + C 4 H 6 (1-butyne) → C 5 H 3 + CH 3 , C 3 H 3 (1-propynyl) + C 2 H 2 (acetylene) → C 5 H 4 + H, C 3 H 3 (propargyl) + C 2 H 2 (acetylene) → C 5 H 5 (cyclopentadienyl and 1-vinylpropargyl), C­( 3 P) + C 4 H 6 (1,3-butadiene, 1,2-butadiene, and dimethylacetylene) → C 5 H 5 + H, C 2 (X 1 Σ g / a 3 Π u ) + C 3 H 6 (propylene) → C 5 H 5 + H, C 2 H (ethynyl) + C 3 H 6 (propylene) → C 5 H 6 + H. ...…”
Section: Introductionmentioning
confidence: 99%
“…3 Alternatively, in deep space, the highly reactive pentynylidyne radical (C 5 H) and the C 5 molecule have been discovered in the envelope of the carbon star IRC+10216; 4−7 the former has also been synthesized in the laboratory via crossed molecular beams of ground-state carbon atoms [C( 3 P)] and diacetylene (C 4 H 2 ). 23 Previously, experimental and theoretical studies of this and other groups have demonstrated that the C 5 H x species (x = 3− 6) can be produced via neutral−neutral bimolecular reactions, such as C( 3 P) + C 4 H 4 (vinylacetylene) → C 5 H 3 + H, C 2 (X 1 Σ g /a 3 Π u ) + C 3 H 4 (methylacetylene and allene) → C 5 H 3 + H, C 2 (X 1 Σ g /a 3 Π u ) + C 4 H 6 ( indicating that the formation mechanisms of C 5 hydrocarbon species are still far from being fully understood. Among the C 5 H x PESs involved in the aforementioned reactions, the C 5 H 7 surface is likely the most intricate one, owing to the high degree of unsaturation of the carbon atoms and a medium number of hydrogen atoms between 0 and 12 (as in fully saturated pentane C 5 H 12 ), which results in a combinatorial growth of possible C 5 skeletons with various positions of double and triple bonds and ring structures and a variety of different placements of seven H atoms on five carbons.…”
Section: ■ Introductionmentioning
confidence: 99%